The philosophy of psychology - Botterill, George (Cambridge University Press, 1999)
This book presents an original and accessible analysis of the relationship between common-sense, or 'folk', psychology and contemporary scientific psychology, focussing on the ways in which cognitive science presents a challenge to our common-sense self image. It is designed as a textbook for upper-level undergraduate and beginning postgraduate students in philosophy and cognitive science. As a text that not only surveys but advances the debates on the topics discussed, it will also be of interest to researchers working in these areas.